Prevalence of anxiety may not be elevated in Thai ovarian cancer patients following treatment - Chittrakul S. (Asian Pacific Organization for Cancer Prevention, 2015)
Background: To compare prevalence of anxiety in ovarian cancer patients following primary treatment to that of normal women and to examine predicting factor. Materials and Methods: In this cross-sectional study, 56 ovarian cancer patients who had primary surgical treatment within the past five years (cancer group) and 56 age-matched women who attended an outpatient clinic for check-ups (non-cancer group) were recruited from June 2013 to January 2014. The hospital anxiety and depression scale (HADS), was used to determine anxiety level of the participants with the score of ≥11 suggestive of anxiety. The prevalence of anxiety symptoms and mean HADS scores for anxiety were compared between the study groups. For those with ovarian cancer, associations of demographic and clinical factors with anxiety was examined. A p-value of <0.05 was considered significant. Results: Participants in the non-cancer group had higher rate of medical comorbidity, higher salary, and more frequent university education. The prevalence of anxiety was not different between the groups, at 7.1% each. The mean HADS scores for anxiety subscale were not significantly different between the groups, 5.0 in the cancer group vs 6.1 in the non-cancer group (p=0.09). On multivariable analysis, no demographic or clinical factors significantly associated with anxiety were identified. For the cancer group, no association between any particular factors and anxiety was demonstrated. Conclusions: The prevalence of anxiety in women with ovarian cancer following primary treatment was comparable to that of normal women seeking routine check-up.